Detection of incipient thermal damage in carbon fiber-bismaleimide composites using hand-held FTIR. (August 2018) - Toivola, Ryan; Afkhami, Farshid; Baker, Shawn; McClure, John; Flinn, Brian D.
Abstract: Bismaleimide (BMI) resins are gaining popularity as matrix materials in carbon fiber composites, especially in high temperature applications, due to their very high glass transition temperatures. Extended elevated temperature exposure can cause a decrease in the matrix dominated properties of BMI-matrix composites due to thermal damage mechanisms that can be chemical (crosslinking, oxidation) or physical (microcracking, delamination) in nature. The chemical damage begins at lower thermal exposures than the physical damage; however standard ultrasonic testing (UT) techniques detect only the physical damage, which is not apparent until a significant loss in matrix dominated properties, such as shear strength, have already occurred. In this study, a thermal damage detection method using a handheld Fourier transform infrared (FTIR) spectrometer to detect chemical changes caused by thermal exposure of Solvay 5250-4/IM7 BMI composite laminates was investigated. Infrared spectra were collected from samples with varying levels of thermal exposure. The spectra were analyzed using multivariate analysis techniques. The FTIR measurements were combined with mechanical property changes measured using short beam strength testing (ASTM D2344-16 ) to develop a model which identified the onset and extent of damage by predicting the change in interlaminar shear strength based on IR spectral changes. We compare our model's performance to ultrasonic inspection as a method for identifying the onset of thermal damage. The FTIR based method detected statistically significant decreases in interlaminar shear strength at thermal exposures well below those causing UT-detectable damage. Highlights: Hand held FTIR spectroscopy and multivariate analysis applied to thermal damage detection in bismaleimide-matrix composite. Strong correlation between IR spectral changes and interlaminar shear strength loss after thermal exposures. A model calibrated using the IR-ILSS correlation is used to predict strengths based on IR spectra after thermal exposure. Model made accurate (R 2 0.96) predictions of ILSS loss after thermal exposure. Model accurately identified ILSS loss at 75 °C lower temperature than ultrasonic C-scan detection of damage.